Multi-stream transmission in MIMO-FBMC systems - Caus, Marius; Perez-Neira, Ana I. (Proceedings of the ... IEEE International Conference on Acoustics, Speech and Signal Processing (1998), 2013)
This paper addresses the design of MIMO precoding and decoding techniques for the filter bank multicarrier (FBMC) modulation. Existing solutions give satisfactory performance in scenarios with high coherence bandwidth channels. With the aim of increasing the robustness against the channel frequency selectivity, we have rethought the problem, which results in a new subband processing. Simulation-based results show that the proposed solution can achieve similar bit error rates as the OFDMsolution, while the spectral efficiency is increased. These results are theoretically justified. As a conclusion, FBMC becomes attractive in frequency selective channels not only because it relaxes the frame synchronization with respect to OFDM, but also because it presents spatial multiplexing competitive results.